2005
DOI: 10.1002/iroh.200310708
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Patterns of Diatoms andLimnodrilus Oligochaetes in a Kenyan Dry Streambed Following the 1999-2000 Drought Conditions

Abstract: Drought is a natural phenomenon experienced by many intermittent and also seasonal lotic systems. It has diverse effects on the structure and distribution of biological communities through habitat transition from wetted to terrestrial conditions. The Njoro River, a tropical stream, was drought-stressed between late 1999 and mid 2000, providing an opportunity to sample and describe the distributional patterns of diatoms and Limnodrilus oligochaetes in the vertical sediment profile. The dispersion of Limnodrilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The Nais-Polypedilum community type, occurring in winter and spring, was followed by the Limnodrilus community type that occurred in autumn and summer. It is not surprising that the Limnodrilus community type occurred during seasons with high inflow discharge and low transparency, because it has been reported that Limnodrilus is tolerant of harsh environments (e.g., MATHOOKO et al, 2005). Before reservoir construction, N. inflata was also the most common species throughout the Yangtze River (LIANG, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The Nais-Polypedilum community type, occurring in winter and spring, was followed by the Limnodrilus community type that occurred in autumn and summer. It is not surprising that the Limnodrilus community type occurred during seasons with high inflow discharge and low transparency, because it has been reported that Limnodrilus is tolerant of harsh environments (e.g., MATHOOKO et al, 2005). Before reservoir construction, N. inflata was also the most common species throughout the Yangtze River (LIANG, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, droughts are known to have a profound impact on the densities and size-or age-structure of populations, on community composition and diversity, and on ecosystem processes (Lake, 2003). For instance, it has been suggested that very few diatom species are abundant and dominant in dry riverbeds, with these remaining species being highly tolerant (Mathooko et al, 2005). Disturbances caused by local flow fluctuations confer heterogeneity to the structure of benthic algae, with successional age being inversely related to disturbance frequency (Ledger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of burrowing taxa is negatively related to discharge and flow velocities in streams and rivers (Masese et al, 2021). In the Njoro River, drying of the river resulted in a tremendous increase in oligochaetes while other sensitive taxa among the EPT were eliminated (Shivoga, 2001;Mathooko et al, 2005). In the Moiben River, the peak of the dry season coincided with a significant decline in sensitive taxa and a proliferation of burrowing and pool-associated taxa, such as Belostomatidae, Corixidae, Gomphidae, and oligochaetes (Masese et al, 2009a;Masese et al, 2009b).…”
Section: Performance Of M-ibimentioning
confidence: 99%